PREDICTION TEKNOLOGI INFORMASI BERPENGARUH PADA MODEL BISNIS KEUANGAN MASA COVID-19 - Hertati, Lesi; Safkaur, Otniel; Syafarudin, Afriapollo; Fery, Irlan (I-Economics, 2020)
Information technology is developing so rapidly virtually, where technology allows users to interact with an environment that is simulated online, a tool that has a number of accurate information that can be accessed online to receive information. Copid_19 information technology has a bad impact on the business activities of small and medium businesses so that the supply of goods becomes using, considering that performance targets other than profit are declining for the company because it does not obtain sales transactions, ultimately the flow of funds from customers is more hampered. The copid-19 outbreak caused it to reduce company financial statements and business practices and profitability according. Copid-19 information technology outbreaks cause customers to make the decision to stay at home with no outside activities, ultimately stopping business practices and other transactions for the company. Public media such as the Web, private social networks, wikis and blogs are important tools for companies to communicate, collaborate and share information about sales through the system and even evaluate directly how sales take place. The data analysis technique used in this study is the Structural Equation Modeling (SEM) technique, in micro and small medium enterprises in Indonesia that are related and 112 samples are collected in micro small and medium businesses spread across Indonesia. The results showed that the copid-19 outbreak information technology was quite influential on the company's financial statements and business practices. Companies must consider losses due to obsolescence of inventory and company income will decrease. This research was conducted at micro small and medium enterprises in Indonesia which were affected by Corona.